Control oriented models of step-up and step-down photovoltaic power systems (2012)
This paper presents the modeling and control of photovoltaic systems considering disturbances in the solar irradiance and the load. Three cases are addressed: step-up/step-down systems using a non-inverting Buck-Boost converter interface, step-down systems using a Buck converter interface, and step-up systems using a Boost converter. Control-oriented models are analytically derived to design controllers that regulate the voltage of the photovoltaic Panel in agreement with the reference provided by a maximum power point tracking algorithm, aimed at maximizing the power production. The proposed models are validated by means of frequency responses analyses, and the designed controllers are validated by means of detailed simulations performed in standard power electronics software. Finally, experimental results illustrate the applicability of the proposed approach to real cases.